Hubungan Self Compassion dengan Stres Akademik pada Mahasiswa yang Bekerja secara Part Time - Beda, Putry Beatrix Rantini; Murti, Heru Astikasari Setya (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Students who work part-time while studying are very susceptible to experiencing academic stress. The high risk of increasing academic stress can have a negative effect on them, both in lectures and work. This study aims to determine the relationship between self-compassion and academic stress in students who work part-time. The research method used in this study uses a quantitative approach with a correlational method. Data collection was carried out on 142 students who work part-time in Central Java. Self-compassion was measured using the Indonesian adaptation of the Self-Compassion Scale (SCS) measuring instrument, namely the Self-Compassion Scale (SWD), academic stress was measured using the Student-life Stress Inventory (SSI) adaptation measuring instrument. Both measuring instruments have reliability and validity values that are suitable for use. Data analysis in this study used the Spearman's rho correlation test with SPSS 24 for Windows. The results of the study showed a significant negative relationship between self-compassion and academic stress (r = - 0.525). It is concluded that the higher the self-compassion, the lower the academic stress in students who work part-time.